ERS/ECDC Statement: European Union standards for tuberculosis care, 2017 update. Issue 5 (17th May 2018) - Migliori, Giovanni Battista; Sotgiu, Giovanni; Rosales-Klintz, Senia; Centis, Rosella; D'Ambrosio, Lia; Abubakar, Ibrahim; Bothamley, Graham; Caminero, Jose Antonio; Cirillo, Daniela Maria; Dara, Masoud; de Vries, Gerard; Aliberti, Stefano; et al.
The International Standards for Tuberculosis Care define the essential level of care for managing patients who have or are presumed to have tuberculosis, or are at increased risk of developing the disease. The resources and capacity in the European Union (EU) and the European Economic Area permit higher standards of care to secure quality and timely TB diagnosis, prevention and treatment. On this basis, the European Union Standards for Tuberculosis Care (ESTC) were published in 2012 as standards specifically tailored to the EU setting. Since the publication of the ESTC, new scientific evidence has become available and, therefore, the standards were reviewed and updated. A panel of international experts, led by a writing group from the European Respiratory Society (ERS) and the European Centre for Disease Prevention and Control (ECDC), updated the ESTC on the basis of new published evidence. The underlying principles of these patient-centred standards remain unchanged. The second edition of the ESTC includes 21 standards in the areas of diagnosis, treatment, HIV and comorbidities, and public health and prevention. The ESTC target clinicians and public health workers, provide an easy-to-use resource and act as a guide through all the required activities to ensure optimal diagnosis, treatment and prevention of TB. The European Union Standards for Tuberculosis Care: a guide for clinicians and public health workers to ensure optimal diagnosis, treatment and prevention of TB http://ow.ly/C80K30jxr1o